Once upon a royal superbaby - O'Malley, Kevin, 1961- (Walker & Co., 2010)
Cooperatively writing a story for school, a girl imagines a king and queen who have a baby named Sweet Piper who can talk to birds, while a boy names the baby Sweet Viper and gives him super-strength, cool wrestling moves, and a motorcycle and sunglasses.